Pengaruh Model Pembelajaran Blended Learning Berbantuan Classroom Terhadap Self Directing Learning (SDL) Dan Hasil Belajar Pendidikan Agama Hindu Dan Budi Pekerti Siswa Kelas VIII SMP N 1 Kubutambahan Tahun Ajaran 2020/2021 - Kadek Benny Wandhana; Putu Wika Putrawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study aims to determine the magnitude of the influence of the Classroom Assisted Blended learning learning model on Self directing learning (SDL) and the Learning Outcomes of Hindu Religious Education and Characteristics of Class VIII Students of SMP N 1 Kubutambahan. This research is a Quasi-Experiments with the design of The Posttest-Only Control-Group Design. The study population was all students of class VIII SMP N 1 Kubutambahan 2020/2021, which consisted of 9 classes with a total population of 279 students. Of the 279 students, 64 students were selected as the sample which was determined by the simple random sampling technique. The data collected is Self directing learning using a questionnaire technique and learning outcomes of Hindu Religion and Character Education using multiple choice tests. Data were analyzed using MANOVA (Multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. The results showed that: First, self-directing learning between students who took the blended learning model was better than students who took the direct learning model (F was 24.455 and Sig = 0.000; p <0.05). Second, the learning outcomes of Hindu religious education and character among students who follow the blended learning model are better than students who follow the direct learning model (F is 15.224 and sig = 0.000; p <0.05). Third, Simultaneously self-directing learning and learning outcomes of Hindu religious education and character among students who follow the blended learning model are better than students who take the direct learning model (F value is less than 0.05). The results of this study recommend that the blended learning model is better used to improve self-directing learning and learning outcomes of Hindu religious education and character than the direct learning model.